2018
DOI: 10.1556/2006.7.2018.70
|View full text |Cite
|
Sign up to set email alerts
|

Tendencies toward Internet-pornography-use disorder: Differences in men and women regarding attentional biases to pornographic stimuli

Abstract: Background and aimsSeveral authors consider Internet-pornography-use disorder (IPD) as addictive disorder. One of the mechanisms that has been intensively studied in substance- and non-substance-use disorders is an enhanced attentional bias toward addiction-related cues. Attentional biases are described as cognitive processes of individual’s perception affected by the addiction-related cues caused by the conditioned incentive salience of the cue itself. It is assumed in the I-PACE model that in individuals pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 63 publications
4
34
0
1
Order By: Relevance
“…In the context of the prevalence of CSB, research indicated that fewer women (as compared to men) reported viewing pornographic materials over the last 6 months, 44 they reported less pornography time use 44,[46][47][48]77 and exhibited lower rates of feeling urges to pornography, 45 a smaller percentage of them self-identified as addicted to pornography based on subjective feeling, 14 and fewer women reported symptoms related to CSB, such as difficulties in controlling sexual thoughts and behaviors, engaging in sexual activity to cope with unpleasant emotional states, and experiencing negative consequences because of these sexual behaviors. [50][51][52][53][55][56][57]63,75,77,89,90,109,111,134,136 It is worth noting that prior research focused on measuring PPU and masturbation and has been conducted almost exclusively in men, and prior work has not included a deeper analysis of patterns of sexual functioning of women who reported issues related to CSB. We also note that the subjective assessment of addiction to pornography does not necessarily reflect a CSBD diagnosis in women.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the prevalence of CSB, research indicated that fewer women (as compared to men) reported viewing pornographic materials over the last 6 months, 44 they reported less pornography time use 44,[46][47][48]77 and exhibited lower rates of feeling urges to pornography, 45 a smaller percentage of them self-identified as addicted to pornography based on subjective feeling, 14 and fewer women reported symptoms related to CSB, such as difficulties in controlling sexual thoughts and behaviors, engaging in sexual activity to cope with unpleasant emotional states, and experiencing negative consequences because of these sexual behaviors. [50][51][52][53][55][56][57]63,75,77,89,90,109,111,134,136 It is worth noting that prior research focused on measuring PPU and masturbation and has been conducted almost exclusively in men, and prior work has not included a deeper analysis of patterns of sexual functioning of women who reported issues related to CSB. We also note that the subjective assessment of addiction to pornography does not necessarily reflect a CSBD diagnosis in women.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, most of which use addiction related experimental paradigms, have sought to better understand the neurobiological underpinnings of CSB. In general, these studies have found that CSB is associated with altered functioning in brain regions and networks implicated in sensitization, habituation, diminished impulse control, and reward processing in patterns like substance, gambling, and gaming addictions (Kowalewska et al, 2018;Stark et al, 2018). In addition, studies looking at dopamine replacement therapies used for individuals with Parkinson's disease have also produced similar patterns of impulse control problems that resemble CSBD (Weintraub et al, 2010).…”
Section: Conceptualizations Of Csbmentioning
confidence: 99%
“…Studies of the cognitive processes underlying responses to appetitive stimuli (e.g., images of alcohol or drugs as related to substance-use disorders) have provided important insight into addictive disorders, identifying implicit responses and biases that likely contribute to the development and maintenance of addictive behaviors (Field & Cox, 2008). Associations between subconscious cognitive biases and addictive behaviors have been found using cross-sectional and prospective experimental designs employing a variety of methods, including joystick tasks (Cousijn, Goudriaan, & Wiers, 2011;Krieglmeyer & Deutsch, 2010;Wiers, Eberl, Rinck, Becker, & Lindenmeyer, 2011), stimulus-response compatibility (SRC) tasks (Field, Kiernan, Eastwood, & Child, 2008;Krieglmeyer & Deutsch, 2010), and visual-probe tasks (Mechelmans et al, 2014;Pekal, Laier, Snagowski, Stark, & Brand, 2018;Schoenmakers, Wiers, Jones, Bruce, & Jansen, 2007). Correlations between cognitive biases, which may reflect motivational tendencies in part generated from learned associations, and addictive behaviors have been observed in both clinical and nonclinical populations in age groups ranging from older children and adolescents to adults (Stacy & Wiers, 2010).…”
Section: Introductionmentioning
confidence: 99%